Cross-sectional study of tuberculosis infection among household contacts of patients with pulmonary tuberculosis - Khan, Muhammad Sohrab; Rabbi, Fazli; Khan, Intikhab Alam; Khan, Uzair Ali (Infectious Diseases Journal of Pakistan, 2025)
Background: Tuberculosis (TB) remains a major public health concern, particularly among household contacts of pulmonary TB patients, where transmission risk is high. This study assessed the prevalence of positive TB screening tests and identified key demographic, behavioral, and environmental risk factors associated with infection. Materials and Methods: The cross-sectional analytical study was done at the Department of Medicine, Mardan Medical Complex, Mardan, from October 2023 to March 2024 including 286 household contacts of confirmed pulmonary TB cases. Participants underwent Tuberculin Skin Test (TST), Interferon Gamma Release Assay (IGRA), chest X-ray, sputum smear microscopy, and GeneXpert MTB/RIF testing. Logistic regression was performed to identify independent predictors of TB infection, adjusting for potential confounders. Results: Positivity rates were 31.5% for TST, 29.7% for IGRA, 17.5% for chest X-ray suggestive of TB, 10.5% for sputum smear microscopy, and 9.8% for GeneXpert. Independent predictors included older age (≥35 years), absence of BCG vaccination, HIV positivity, current smoking, close sleeping proximity to the index patient, and poor household ventilation (all p < 0.05). Diabetes showed borderline significance, while sex and former smoking were not significant. Conclusion: TB infection among household contacts is influenced by a combination of biological, behavioral, and environmental factors. Targeted interventions, including vaccination, smoking cessation, HIV care, and improvements in household ventilation, could substantially reduce transmission risk. Keywords: Tuberculosis, Household contacts, BCG vaccination, HIV, Smoking, Ventilation.